Sleep quality, perceived stress, and quality of life of healthcare professionals working in direct contact with COVID-19 (+) patients: A comparative study - Barut, Sümeyye; Uçar, Tuba; Baransel, Esra Sabancı (Selçuk BAŞAK, 2021)
Background/Aim: Healthcare workers can be psychologically and physically affected by the COVID-19 pandemic. This study was conducted to evaluate the sleep quality, perceived stress, and quality of life of healthcare professionals during the COVID-19 pandemic. Methods: This cross-sectional and comparative study was conducted with employees of a city hospital in Turkey between 01-20 January 2021. Personal Information Form, Jenkins Sleep Scale, Perceived Stress Scale, and Quality of Life Test Short Form-36 (SF-36) were used to collect data during face-to-face interviews conducted with the hospital staff by the researchers. The sample of the study consisted of a healthcare team providing service for COVID-19 patients in the city hospital (Group 1) and a healthcare team working without direct contact with COVID-19 patients (Group 2). The results obtained from the study were compared between these two groups. There were 213 volunteers in Group 1, and 163 volunteer healthcare workers (doctors, nurses, midwives, medical secretaries, patient transfer staff, and patient support staff) in Group 2. Results: Sleep problems and stress levels were significantly higher among healthcare professionals who had direct contact with COVID-19 (+) patients compared to those who did not (P
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi